Rewrite the fractions to have a common denominator to find the difference:
2/3 = 4/6
Difference = 4/6-5/6 = -1/6
Sequence formula = an = a1 + d(n-1)
A1 is the first term 5/6
And d = -1/6
Sequence = 5/6 -1/6(n-1)
Simplify to get an =(-n +6)/6
The coefficient of y∧15×∧2 in expansion of (y∧3+x)∧7 is (15×2)+(3×7)= 51
90% in a fraction is the same as 90/100 simplified, is 9/10.
Hope this helps
192
Next time try to add more points bc i worked so hard to answer this
Answer:
465 is the total points he got and he solved 14 in part A and 2 in part B
hope it helps you
mark me as brainlist
thank you